Discovery of New α-Glucosidase Inhibitors: Structure-Based Virtual Screening and Biological Evaluation - Liu, Shan-Kui; Hao, Haifang; Bian, Yuan; Ge, Yong-Xi; Lu, Shengyuan; Xie, Hong-Xu; Wang, Kai-Ming; Tao, Hongrui; Yuan, Chao; Zhang, Juan; Zhang, Jie; Jiang, Cheng-Shi; et al. (Frontiers in Chemistry, 2021)
α-Glycosidase inhibitors could inhibit the digestion of carbohydrates into glucose and promote glucose conversion, which have been used for the treatment of type 2 diabetes. In the present study, 52 candidates of α-glycosidase inhibitors were selected from commercial Specs compound library based on molecular docking–based virtual screening. Four different scaffold compounds (7, 22, 37, and 44) were identified as α-glycosidase inhibitors with IC50 values ranging from 9.99 to 35.19 μM. All these four compounds exerted better inhibitory activities than the positive control (1-deoxynojirimycin, IC50 = 52.02 μM). The fluorescence quenching study and kinetic analysis revealed that all these compounds directly bind to α-glycosidase and belonged to the noncompetitive α-glycosidase inhibitors. Then, the binding modes of these four compounds were carefully investigated. Significantly, these four compounds showed nontoxicity (IC50 > 100 μM) toward the human normal hepatocyte cell line (LO2), which indicated the potential of developing into novel candidates for type 2 diabetes treatment.